Uganda : Sixth Review Under the Policy Support Instrument and Request for a One-Year Extension-Press Release; Staff Report; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2016)
This paper review Uganda's economic performance under the program supported by the Policy Support Instrument. Despite sluggish growth in credit to the private sector, GDP growth has been supported by the implementation of large public investments. Inflation has started to decelerate toward the medium-term target, allowing for monetary policy easing. Adverse weather developments, regional and global-political and economic uncertainties, and post-election fiscal pressures may challenge the achievement of short-term growth and inflation objectives. However, provided progress on structural reforms is accelerated, the medium-term outlook remains positive, supported by future oil production, increased regional integration and inter-regional trade, and implementation of significant infrastructure projects.